Angelina takes a bow - Holabird, Katharine (Angelina Ballerina, 2012)
"Angelina is excited to have the lead in her school's ballet! But she's sad that she spends most of the ballet sleeping instead of dancing. Can Ms. Mimi convince Angelina that her role is important?"--P.[4] of cover.